2018
DOI: 10.4049/jimmunol.1701179
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of B Cells and Dendritic Cells from Lupus-Prone Mice to CD4+ T Cell Polarization

Abstract: Mouse models of lupus have shown that multiple immune cell types contribute to autoimmune disease. This study sought to investigate the involvement of B cells and dendritic cells in supporting the expansion of inflammatory and regulatory CD4 T cells that are critical for lupus pathogenesis. We used lupus-prone B6.NZM2410.Sle1.Sle2.Sle3 (TC) and congenic C57BL/6J (B6) control mice to investigate how the genetic predisposition of these two cell types controls the activity of normal B6 T cells. Using an allogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
0
14
1
Order By: Relevance
“…Although the same general mechanisms regulate the activation of all T-cell subtypes (effector and regulatory) it is worth emphasizing that in the lupus autoimmunity environment, there is favoritism of self-reactive effector (4, 73, 99); with the detriment of regulatory cells (17, 97, 100). One of the bases of this polarization lies in the fact that there are plasticity and reciprocity between Th17 and Treg (100-102), a balance influenced by various factors (103), and the inflammatory and autoimmunity environment of lupus favors to the side of the Th17 cells (2,79,101). Added to Th17/IL-17 axis overactivity, LN is characterized by decrease, suppression, or dysfunction of Treg cells (57, 104) and impairment of other protective factors like IL-2 (97) and IL-10 (105, 106).…”
Section: Th17 Polarization In Sle and Related Immunes Imbalancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the same general mechanisms regulate the activation of all T-cell subtypes (effector and regulatory) it is worth emphasizing that in the lupus autoimmunity environment, there is favoritism of self-reactive effector (4, 73, 99); with the detriment of regulatory cells (17, 97, 100). One of the bases of this polarization lies in the fact that there are plasticity and reciprocity between Th17 and Treg (100-102), a balance influenced by various factors (103), and the inflammatory and autoimmunity environment of lupus favors to the side of the Th17 cells (2,79,101). Added to Th17/IL-17 axis overactivity, LN is characterized by decrease, suppression, or dysfunction of Treg cells (57, 104) and impairment of other protective factors like IL-2 (97) and IL-10 (105, 106).…”
Section: Th17 Polarization In Sle and Related Immunes Imbalancesmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a disease characterized by hyperreactivity to the self, with the polarization of the immune response to a proinflammatory profile (1,2), autoantibodies production (3), immune complex formation (4) and deposition in tissues (5). It also occurs with local production of inflammatory mediators, and additional recruitment of inflammatory cells, resulting in tissue damage in various organs (6).…”
Section: Introductionmentioning
confidence: 99%
“…These cells, regardless the subpopulation, while dysregulated are anticipated to be responsible for the tolerance breakdown resulting in autoaggression (24). Abnormalities in circulating DCs function have been linked to the systemic manifestation of lupus, throughout the interplay with both B cells (25) and T cells (26). Our previous study revealed that molecular alterations in mDCs (CD1c+) and pDCs from lupus patients significantly influence the hyperactivated B cells, mainly through secretory and expression activity [unpublished data].…”
Section: Discussionmentioning
confidence: 99%
“…Pbx1d-Tg mice were bred with B6.Foxp3 YFPCre mice to generate the Treg cell reporter strain, Pbx1d-Tg.Foxp3 YFPCre . For in vitro Tfh experiments, Pbx1d-Tg mice were bred with B6.IL-21 VFP mice (57) to generate the IL-21 reporter strain, Pbx1d-Tg.IL-21 VFP .…”
Section: Methodsmentioning
confidence: 99%